Pengaruh Penerapan Model Inkuiri Terbimbing Berbasis Video Pembelajaran terhadap Hasil Belajar Siswa Kelas XI Sma pada Materi Laju Reaksi - Z Pasaribu, Marisa; Nainggolan, Bajoka (Jurnal Indonesia Sosial Sains, 2022)
This study aims to (1) determine the effect of the application of guided inquiry model based on video learning on improving student learning outcomes. (2) find out whether students' chemistry learning outcomes using instructional video media are higher than students' chemistry learning outcomes taught using powerpoint media. This research was conducted in November-December 2021 at SMA N 1 Sunggal involving experimental class I and experimental class II. The two classes were given different treatment, the experimental class I was given learning using a guided inquiry model and learning videos, the experimental class II was given learning using a guided inquiry model and powerpoint. This research is a quasi-experimental research design with the Nonequivalent control group design model. From the results of the study, the average pretest value of the experimental class I was 43.47 and the average value of the experimental class II was 43.19. After being given treatment, the two classes were then given a posttest to determine learning outcomes, the average posttest score for the experimental class I was 83.33 and the experimental class II was 79.16. The results showed that both classes experienced an increase in learning outcomes, the experimental class I experienced an increase in the value of 39.86 and the experimental class II by 35.19. The N-Gain data for the experimental class I was 71% and the experimental class II was 64%. It can be concluded that the guided inquiry model and learning video media can have an influence on student learning outcomes in the form of increasing learning outcomes.